Profil Stres Ibu Dalam Mendampingi Anak Belajar (Studi Kualitatif pada Ibu Bekerja dan Ibu Tidak Bekerja) - Fitra Marsela; Nabila Arshadina; Nurhasanah Nurhasanah (Prodi Bimbingan dan Konseling Islam, 2022)
Mother's stress in accompanying children to study is a condition of pressure/tension experienced by mothers in carrying out their responsibilities as working mothers and mothers who do not work in accompanying children to study. This study aims to describe the stress profile of working and non-working mothers in accompanying children to study at SDN 22 Banda Aceh. The type of research used is descriptive with a qualitative approach. There were 12 research subjects consisting of 6 working mothers and 6 non-working mothers. Data were collected through interviews and analyzed using descriptive qualitative. The results showed that the physical stress experienced by working mothers had more complaints than mothers who did not work in accompanying children to study, namely experiencing dizziness or headaches, fatigue in accompanying children to study, and disrupted mother's sleeping hours. Cognitive stress of non-working mothers has more complaints than working mothers in assisting children, such as disturbed concentration, difficulty balancing concentration, difficulty managing time, and lack of understanding of children's learning material. Emotional stress experienced by working mothers and non-working mothers shows the same results, namely feeling pressured when accompanying children, anger when children are difficult to teach, feelings of guilt, and despair. Meanwhile, the stress of social behavior of non-working mothers shows more complaints than working mothers, including acts of despair committed, lack of husband or family support, acts of violence when children are difficult to teach, and punishing children. The conclusion of this study is that non-working mothers experience more stress complaints than working mothers.